Production of Bioethanol from Bunches of Palm Oil Using Purification Equipment with Bioethanol Traps - Devina Sanchia Samosir; Yohandri Bow; Abu Hasan (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Due to the rising demand for motor vehicle fuel, Indonesia's requirement for fossil fuels rises by an average of 10% annually. The supply of fossil energy, which serves as the primary raw material for generating fuel oil, is negatively correlated with the demand for fuel (BBM). Fresh Fruit Bunches (FFB), Empty Fruit Bunches (EFB), and fiber were the types of oil palm bunches employed in this investigation. EFB and fiber are industrial by products that are currently being used inefficiently and frequently pollute the environment. This trash is still only very minimally processed; it is still stored, burned in the incinerator, used as mulch on oil palm fields, and composted. 51.2 percent cellulose and 16.30 percent lignin are both present in EFB. Lignin makes up 20.0 percent of fiber, whereas cellulose makes up 57.0 percent. Through chemical and enzymatic procedures, this cellulose content may be exploited as a source of reducing sugars. FFB is used as a benchmark to evaluate how effectively the prototype tool works. Different kinds of high-quality bioethanol are produced from each raw source. Different kinds of high-quality bioethanol are produced from each raw source. Fresh Fruit Bunches (FFB), which have a refractive index of 1.35676 and a volume of 2,192 ml, are the best quality of bioethanol made from raw materials. The findings demonstrated that varied volumes and refractive indices were produced depending on how raw materials were treated. The quality generated improves with increased treatment volume. Alkaline delignification was followed by acid delignification to get the optimum grade. Empty Fruit Bunch (EFB) material, which had a refractive index of 1.34376, 2,105 ml of bioethanol, and a 68.15 percent ethanol concentration. This study is unique in that it includes a bioethanol trap to quicken the conversion of steam into liquid bioethanol. Condensation is completed in 15–20 minutes less time thanks to the bioethanol trap.